2018
DOI: 10.1177/0269215518815931
|View full text |Cite
|
Sign up to set email alerts
|

A study of the description of exercise programs evaluated in randomized controlled trials involving people with fibromyalgia using different reporting tools, and validity of the tools related to pain relief

Abstract: Rationale: Exercise programs for the management of fibromyalgia are well recognized as being effective. However, the incomplete descriptions of exercise programs make replication and implementation difficult. Also, existing reporting tools have not been validated in relation to pain relief as well as with each other. Objectives: This study aimed to evaluate the description of exercise programs in randomized control trials for the management of fibromyalgia using different assessment tools, and the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…These results align with the findings of Hay-Smith et al, 37 as well as other studies that have shown poor exercise-based intervention reporting in the physiotherapy management of pelvic floor and other conditions. [4][5][6][7][8][9][10][11] This trend across the physiotherapy literature demonstrates the necessity for the systematic use of standardized instruments such as CERT and TIDieR to detail, as much as possible, all of the parameters of an exercise intervention to facilitate best practices implementation. The most poorly reported items on the three different instruments suggest that researchers should pay more attention to describing the following components of PFMT exercise interventions for UI in women:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results align with the findings of Hay-Smith et al, 37 as well as other studies that have shown poor exercise-based intervention reporting in the physiotherapy management of pelvic floor and other conditions. [4][5][6][7][8][9][10][11] This trend across the physiotherapy literature demonstrates the necessity for the systematic use of standardized instruments such as CERT and TIDieR to detail, as much as possible, all of the parameters of an exercise intervention to facilitate best practices implementation. The most poorly reported items on the three different instruments suggest that researchers should pay more attention to describing the following components of PFMT exercise interventions for UI in women:…”
Section: Discussionmentioning
confidence: 99%
“…The training was provided by a third physiotherapist and doctoral candidate (author's initials removed to protect blinding) in Rehabilitation Sciences who had used these scales in four previous evaluations of exercise reporting in other areas of physiotherapy. [5][6][7] To ensure proper understanding and application, three RCTs describing exercise interventions for knee osteoarthritis, that were previously assessed by (author's initials removed to protect blinding), were used to assess each reviewer's readiness to begin the data extraction process. Once ready, each reviewer independently scored the included PFMT trials with each of the three different exercise-reporting tools, blinded to the other reviewer's scores.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management of FM is based on symptomatic multidisciplinary treatment through pharmacologic and non-pharmacologic strategies. Among non-pharmacologic treatments, exercise, cognitive behavioral therapy, and education have the strongest efficacy evidence (10,11). Bote and colleagues demonstrated that mild cycling improves the inflammatory and stress status of FM.…”
Section: Introductionmentioning
confidence: 99%